THE INFLUENCE LIFESTYLE, GROUP PREFERENCE, PERCEPTION BRAND LUXURY AND PRODUCT QUALITY TOWARD CONSUMER WILLINGNESS TO PAY ( Study of consumer iPhone at Malang ) - Ghifari Alief Putra (Manajemen Bisnis, 2016)
The purposes of this study was determine the influence of lifestyle, group preference, perception brand luxury and product quality toward consumer willingness to pay on iPhone product. The population in this study consist of society in Malang that buy iPhone product, which the value was unknown. Based on Maholtra analysis, number of sample are 85 respondent. This study use purposive sampling as the sampling technique. Data analysis was used in this study was multiple regression analysis. The result of this study shows that lifestyle, group preference influence have significant toward consumer willingness to pay partially. In addition, the results of the F test describes that  lifestyle, group preference, brand luxury and product quality influence on have significant consumer willingness to pay simoultaneosly